Diabetic intestinal growth adaptation and glucagon-like peptide 2 in the rat: effects of dietary fibre. Issue 5 (1st November 1999) - Thulesen, J; Hartmann, B; Nielsen, C; Holst, J J; Poulsen, S S
Abstract : BACKGROUND/AIMS: Dietary fibre influence growth and function of the upper gastrointestinal tract. This study investigates the importance of dietary fibre in intestinal growth in experimental diabetes, and correlates intestinal growth with plasma levels of the intestinotrophic factor, glucagon-like peptide 2 (GLP-2). METHODS: Male Wistar rats were randomised to the following groups: two streptozotocin-diabetic and two control groups fed either a fibre-containing or a fibre-free diet for three weeks. Intestinal weight, length, and morphometric data (villus height, villus area, crypt depth) were measured. Blood samples were obtained after two weeks for measurement of GLP-2 and enteroglucagon (glicentin, oxyntomodulin). RESULTS: The mean daily consumption of food in the two diabetic groups was 40% higher than in controls. In diabetic rats fed fibre, the increase in intestinal weight from day 0 to 20 was sixfold greater than that of the controls and small intestine weight per cm length was increased by 50%. In the diabetic rats fed a fibre-free diet, intestinal growth was 30% less than in diabetic rats fed fibre, and intestinal weight increased only threefold compared with controls. Morphometric data showed that the intestinal increase in diabetic rats fed fibre was due primarily to growth of the mucosal layer. Villus height and crypt depth increased 60% and 40% respectively, but by only 20% in fibre-free diabetic rats. The plasma levels of GLP-2 parallelled diabetic intestinal growth, whereas plasma levels of enteroglucagon increased regardless of the extent of intestinal growth. CONCLUSIONS: Intestinal growth in experimental diabetes is strongly influenced by the presence of dietary fibre. The effect may be mediated by GLP-2.